Transforming Africa's Rice value chains: TAAT 2 achievenments, lessons and scaling pathways - Ndindeng, Sali Atanga (AfricaRice and CGIAR, 2025)
The TAAT-II Rice Compact, led by AfricaRice in partnership with NARES and value-chain stakeholders across seven African countries, made significant progress in scaling climate-smart rice technologies, strengthening national seed systems, modernizing post-harvest practices, and institutionalizing digital innovation. The program directly contributed to national food security strategies and AfDB’s Feed Africa objectives by delivering evidence-based, market-relevant solutions that improved productivity, resilience, and value-chain performance. Across Benin, Cameroon, Côte d’Ivoire, Ghana, Madagascar, Senegal, and Uganda, TAAT-II reached over 4.09 million farmers, disseminated more than 26 high-impact innovations, and generated 21,487 jobs, the majority for women and youth. Productivity rose from 3.4 t/ha to 5.38 t/ha, driven by the adoption of climate-resilient varieties, improved agronomic practices, mechanization, and post-harvest technologies. Certified seed production expanded to 6,091 MT, supported by stronger Early Generation Seed (EGS) pipelines, enhanced seed quality assurance, and the professionalization of seed enterprises. Mechanization and post-harvest interventions—particularly ASI threshers, GEM parboilers, hermetic storage, and improved drying systems—significantly reduced losses, improved head rice yield, and elevated the quality and market competitiveness of locally produced rice. Women and youth were central beneficiaries, leading parboiling clusters, operating mechanization services, and engaging in digital data collection. Digital transformation emerged as a major achievement, with 15,853 farmers registered, 3,678 fields mapped, and 31 SMEs onboarded into the eProd platform. Digital profiling improved traceability, strengthened seed and grain inventory management, enhanced cooperative governance, and supported MELIA harmonization across countries. SMS advisory messages improved farmer responsiveness to training, seed availability, and climate advisories. Institutionally, TAAT-II strengthened 433 organizations, including NARES, seed enterprises, processors, cooperatives, and Innovation Platforms (IPs). These multi-actor platforms facilitated varietal demonstrations, market linkages, training rollouts, and policy engagement. National seed roadmaps were advanced in nine countries, providing a strategic pathway for long-term seed system reform. The program successfully addressed major climate and market challenges. Through targeted deployment of drought-, cold-, submergence-, and salinity-tolerant varieties, TAAT-II helped stabilize production in a period marked by floods, drought episodes, cold spells, and inputmarket disruptions. Engagement with millers, traders, and processors strengthened commercial integration and accelerated adoption of quality-enhancing technologies. TAAT-II is now positioned to transition into a stronger, more integrated TAAT-III phase by deepening EGS capacity, scaling hybrid rice, expanding mechanization and drying technologies, strengthening digital systems, and institutionalizing IPs within national extension structures. Strategic priorities include financing seed and mechanization infrastructure, empowering SMEs, integrating climate information services, and expanding women- and youth-led enterprises. Overall, TAAT-II has proven that when climate-smart technologies, robust seed systems, digital tools, and institutional partnerships are combined, rice self-sufficiency becomes achievable at scale. AfricaRice’s leadership has ensured that TAAT-II outcomes extend beyond project outputs to lasting systems transformation—anchored in national policy frameworks, embedded in value chains, and driven by farmer and market demand.